2023
DOI: 10.5603/fm.a2022.0008
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced alterations in the blood-nerve barrier: effects of combination of vitamin B1, B6 and B12

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This produced a retention of food that led to stomach enlargement. It is known that peripheral nervous failure (dysautonomia) can be produced by toxic molecules, in this case, by cisplatin [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…This produced a retention of food that led to stomach enlargement. It is known that peripheral nervous failure (dysautonomia) can be produced by toxic molecules, in this case, by cisplatin [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the pericytes seemed to have a normal appearance. In comparison, Tothonglor et al 47 reported that cisplatin affected BNB via the separation of pericytes from the thicker BM. When S1P binds with the S1P receptor 2, there might be cross‐talk with vascular endothelial growth factor to stimulate inflammation 18,19 .…”
Section: Discussionmentioning
confidence: 96%
“…Chemotherapy-induced peripheral neuropathy (CIPN) is one of the most common long-term toxicities. Combination of vitamins (B1 : B6 : B12 ¼ 100 : 100 : 1) was demonstrated to reduce CIPN by inhibiting the toxic effects [22]. Combination of these vitamins may play more important roles in supporting the activity of a suffering nerve and in the therapeutic management of neuropathies [23,24].…”
Section: Combination Of B Vitaminsmentioning
confidence: 99%